Students’ Perception on Social Media to Increase Usage Speakings Skill at SMP Kemala Bhayangkari 7 Porong - Febriani, Intan Rahma; Fediyanto, Niko (Journal of Technology and System Information, 2024)
There are many options for increasing one's education, particularly acquiring English. The realization that many students' confidence in public speaking increased after utilizing social media prompted this study. This study was designed to examine and evaluate students' speaking abilities. In this study, 59 pupils from class VII-1 of SMP Kemala Bhayangkari 7 Porong were given a results questionnaire with alternative responses. The purpose of this research is to determine whether social media may aid in English learning, particularly in increasing students' speaking abilities. In this study, the Google form-based survey media questionnaire was used as a questionnaire, and the approach used consisted of 5 questions to determine whether social media could help students' speaking skills in class VII-1 SMP. The results of the poll, according to Kemala Bhayangkari 7 Porong, show that social media can help students learn English, especially speaking skills, and improve students' speaking skills.